Time to recovery of COVID-19 patients and its predictors: a retrospective cohort study in HUCSH, Sidama, Ethiopia - Ali B. Anteneh; Zeytu Gashaw Asfaw (BMC Public Health)
Abstract Introduction The 2019 COVID-19 pandemic had a global impact, leading to numerous deaths, long recovery times, and economic challenges worldwide, especially in countries with limited financial resources like Ethiopia. In Ethiopia, Hawassa lacks viral shedding information. Identifying predictors can help ease economic impact of illness.Therefore, this research aimed to examine the demographics, clinical features, and recovery time of COVID-19 patients, as well as determine predictive markers for severe adverse outcomes. Methods Study at Hawassa University Comprehensive Speciality Hospital COVID-19 quarantine and therapy facility in Ethiopia (Sep 24, 2020 - Nov 26, 2021) with 804 patients. Extracted clinical, epidemiological, demographic info from medical records. Researchers used statistical tests like T tests, Chi-square tests, and Fisher’s exact tests to analyze relationships between variables. They also used a Cox PH model to identify risk factors for COVID-19 patient recovery time. Significance level was set at 0.05 for all analyses. Results Out of 804 COVID-19 patients, 74% recovered at an average age of 44.8 years, with 64.1% being male. Severe and critical cases were 24.1% and 21.4% of the population, respectively, with only 16.0% of critical cases and 19.5% of severe cases recovering. Average length of stay was 12.3 days. 88.4% of recovered patients had symptoms, with chest pain (66.7%), cough (64.4%), shortness of breath (59.2%), and fever (57.1%) being common. Nearly half had comorbidities, with diabetes (15.9%) and hypertension (15.2%) prevalent. Male patients had higher recovery rates, while severe/critical patients had lower rates. Patients over 39 age category had lower recovery chance. Existence of at least one comorbidities, diabetes, fever, and hypertension impacted recovery. Fever with gender and shortness of breath affected recovery. Assumptions were met with no multicollinearity. Conclusions Recent studies found that about 95% of COVID-19 patients recover within 30 days, with a median of 12 days. Severe cases, elderly, and those with comorbidities may take longer to recover. By effectively managing hypertension and diabetes, individuals can improve their prognosis and facilitate a quicker recovery. Public health concerns persist regarding COVID-19, especially for comorbidities like diabetic and hypertension. Early detection of fever and treatment of hypertension may expedite recovery.